That's AWESOME: Awareness while experiencing and surfing on movies through emotions - Chambel, T.; Arriaga, P.; Fonseca, M. J.; Langlois, T.; Postolache, O.; Ribeiro, C.; Piçarra, N.; Alarcão, S. M.; Jorge, A. (IMXw '23: Proceedings of the 2023 ACM International Conference on Interactive Media Experiences Workshops, 2023)
This paper presents the AWESOME research project: Awareness While Experiencing and Surfing On Movies through Emotions, which focused on the role of emotions in movies, aiming to enhance viewers' emotional awareness while searching, accessing and watching movies. The project addressed challenges such as capturing viewers' emotional responses, and analyzing movie content based on subtitles, audio, and video. Through a multimethod approach and combining distinct measurements, the project gained insights into viewers' emotions, developed algorithms for estimating emotions, and created interactive tools to annotate and access movies based on emotions. User satisfaction with the tools provided further evidence about the relevance of taking emotions into account and providing an effective support. Through this paper, we present an overview about the motivations underlying the AWESOME project, its main goals, tasks and contributions, and highlight directions for future work.